The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/1983-21252023v36n116rc
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange, growth, and production of cotton genotypes under water deficit in phenological stages

Abstract: Cotton cultivation in the Brazilian Northeast region faces water scarcity problems caused by the irregularity of the rainy season, leading to losses in yield. In this context, the objective of the present study was to evaluate the gas exchange, growth, and production of colored-fiber cotton genotypes under water stress, varying the water deficit management strategies in the different phenological stages of the plant. The study was carried out in the experimental area of the Federal University of Campina Grande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Thus, it can be seen that ‘BRS Jade’ had greater production potential in both cycles. This is justified by the genetic constitution inherent to the genotype, allowing it to have superior agronomic characteristics when compared to the other genotypes studied [ 42 ], favoring the use of ‘BRS Jade’ as a genetic material suitable to sustainable agricultural exploitation [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be seen that ‘BRS Jade’ had greater production potential in both cycles. This is justified by the genetic constitution inherent to the genotype, allowing it to have superior agronomic characteristics when compared to the other genotypes studied [ 42 ], favoring the use of ‘BRS Jade’ as a genetic material suitable to sustainable agricultural exploitation [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…When comparing the assimilation rate of plants irrigated with water of 3.5 dS m -1 to that of plants that received water of 0.3 dS m -1 , a decrease of 56.33% was observed. The reduction in the photosynthesis rate of sour passion fruit plants under salt stress conditions is related to the action of stomatal and non-stomatal factors, such as the restriction of CO 2 diffusion in the mesophyll cells and a decrease in the affinity of ribulose-1,5-biphosphate carboxylase-oxygenase (RuBisCO) with CO 2 (Soares et al, 2023), including changes in chlorophyll and carotenoid concentrations (Dias et al, 2019;Diniz et al, 2020). Silva et al (2019), when evaluating the gas exchange of passion fruit as a function of irrigation with saline waters (ECw ranging from 0.7 to 2.8 dS m -1 ), observed that the lowest CO 2 assimilation rate (8.18 μmol CO 2 m -2 s -1 ) was obtained in plants irrigated with water of 2.8 dS m -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Although cotton plants are relatively tolerant to water deficits, the expansion of cotton farming in the Brazilian semiarid region is constrained by local water conditions. Research on cotton crops under water restrictions has shown that water scarcity, particularly during critical phases like flowering and boll formation, directly impacts plant growth, development, and ultimately the productivity and quality of the fibers (Cordão et al, 2018;Maniçoba et al, 2021;Soares et al, 2023).…”
Section: Introductionmentioning
confidence: 99%